Noninvolvement of beauvericin in the entomopathogenicity of Beauveria bassiana. - Champlin, F R (1979)
Development of a microbiological autobiographic assay procedure permitted a detailed investigation of the possible role of beauvericin (a toxic ionophoric antibiotic produced by Beauveria bassiana) in the entomopathogenicity of B. bassiana against corn earworm (Heliothis zea) larvae. Analysis of spent media of B. bassiana and the hemolymph of infected and moribund larvae revealed that beauvericin was not present in a soluble form during the time that most (about 90%) larvae died of fungal infection (4 days). Intrahemocoelic injections of up to 6 micrograms of synthetic beauvericin failed to induce any deleterious effects. In addition, although methanol-soluble ionophores, such as valinomycin and bassianolide, were toxic to corn earworm larvae, no methanol-soluble toxin could be detected in the hemolymph of moribund larvae.